Availability and procurement cost analysis of fresh Norway spruce (Picea abies) logging residue chips and needles from regeneration fellings to biorefining in Finland - Laitila, Juha; Jylhä, Paula; Brännström, Hanna; Ranta, Tapio; Asikainen, Antti (Elsevier, 2025)
Logging residues of Norway spruce (Picea abies), especially needles with a high extractives content, show potential as a raw material for biorefineries. The present study aimed to assess the availability and procurement costs of fresh Norway spruce logging residue chips and needles for five hypothetical sites in different parts of Finland through a region-level system analysis. The raw material potential and sourcing costs were calculated for an area within a 100-km transport distance along the existing road network from the five hypothetical delivery points. The yield and cost calculations were based on stand data from three major forest industry companies. The procurement cost simulations included harvesting, chipping, chip transportation, and screening of the chips at the delivery point. Both accumulation and procurement costs were calculated per dry tonne. The highest marginal procurement costs of logging residue chips were within the range of 98.8–100.5 € per dry tonne, when their technical harvesting potential varied between 47,000 and 198,000 dry tonnes per year among the five delivery points. Compared to logging residue chips, the procurement cost for the needles was 11.1–16.6 € per dry tonne higher when the recovery rate of needles by screening was assumed to be 50 % of the total which was 15,000–63,000 dry tonnes per year. Procurement costs were very sensitive to the recovery rate of the needles, which affects both the screening cost and the accumulation of needle feedstock.
Keywords: crown biomass; pre-feasibility study; needles; cost curve; screening; techno-economical potential; cascading use